Molecular epidemiological and virological study of dengue virus infections in Guangzhou, China, during 2001–2010 - Jiang, Liyun (BioMed Central, 2013)
BACKGROUND: Dengue virus (DENV) infection is the most prevalent arthropod-borne viral infection in tropical and subtropical regions worldwide. Guangzhou has the ideal environment for DENV transmission and DENV epidemics have been reported in this region for more than 30 years. METHODS: Information for DENV infection cases in Guangzhou from 2001 to 2010 were collected and analyzed. The DENV strains were cultured and isolated from patients’ sera. Viral RNA was extracted from cell culture supernatants. cDNA was synthesized by reverse transcription PCR. Phylogenetic trees of four DENV serotypes were constructed respectively. RESULTS: In total, 2478 DENV infection cases were reported; 2143 of these (86.43%) occurred during 3 months of the year: August, September and October. Of these, 2398 were local cases (96.77%) and 80 were imported cases (3.23%). Among the imported cases, 69 (86.25%) were from Southeast Asian countries. From the 90 isolated strains, 66.67%, 3.33%, 14.44%, and 15.56% belonged to DENV serotypes 1, 2, 3, and 4, respectively. DENV-1 was predominant in most of the years, including during 2 outbreaks in 2002 and 2006; however, none of the strains or genotypes identified in this study were found to be predominant. Interestingly, DENV strains from different years had different origins. Moreover, the strains from each year belonged to different serotypes and/or genotypes. CONCLUSIONS: Southeast Asia countries were found to be the possible source of DENV in Guangzhou. These findings suggest that there is increasing diversity in DENV strains in Guangzhou, which could increase the risk of DENV outbreaks in the near future.